Advances in the practice of microsurgery: focusing on free anterolateral thigh perforator flap (Medical Journal of Indonesia, 2007)
The purpose of this paper was to discuss an overview of the current clinical practice of microsurgery with a specific use of free anterolateral flap as one of the commonest flaps used in reconstructive surgery. A systematic review was performed through all English publication that goes to Pubmed during the period of 1997 to 2006 using keywords: "anterolateral thigh perforator flap." The studies involved were retrospective case reviews on using microsurgical technique and involves free anterolateral thigh flap only without muscle involvement. Evaluation was done to search the indications, contraindications, area or organ to reconstruct, the cause of defects need reconstructive surgery, morbidities, functional and aesthetic results, techniques in regard of suture material, and instruments. Using 7th edition EndNote program, 230 abstracts were successfully retrieved in term of "anterolateral thigh perforator flap" of ANY FIELD and Boolean logic OR. Fifty six abstracts from many journals matched the criteria. Due to our limitation to get all of those articles, finally, 8 articles from Plastic and Reconstructive Surgery became the resources of this paper. The overall success rate in terms of flap viability is 98% (525 from 535 flaps) with partial necrosis is as low as 2.2% (12 from 535 flaps). Thinning procedure is commonly applied with regards of the thin flap needed. The recipient sites from 8 articles varies and can be any part of the body includes facial, neck, pharyngoesophagus, breast, upper and lower extremity. Four out of 8 papers mentioned functional evaluation and all stated satisfactory to excellent outcome. There are also 4 papers mentioning the aesthetic evaluation. Overall evaluation was mentioned as good to excellent. It is concluded that free anterolateral thigh perforator flap is a well established choice in most soft tissue reconstruction. It can be indicated to any area needed reconstruction especially head and neck, extremity, and go beyond conventional for breast reconstruction. It has also superior result in pharyngoesophageal reconstruction. (Med J Indones 2007; 16:245-50)